Effect of Food Quality and Physical Environment on Robucca Café Customer Satisfaction - Putra, Ferdinand Vincentius Djaja (Review of Management and Entrepreneurship, 2024)
In today’s competitive hospitality industry, where customer satisfaction is a crucial driver of business success, identifying the factors that significantly impact satisfaction levels is crucial for the cafe’s management to make informed decisions and enhance the overall customer experience. This research aims to investigate the impact of the physical environment and food quality at Robucca Cafe on customer satisfaction, focusing on identifying which variable among these factors has the most significant influence on consumer satisfaction. This study employed a quantitative research approach, and the participants were customers of Robucca Café. An accidental sampling method was used to select respondents among those visiting Robucca Café, resulting in 60 respondents forming the sample. The data collected will be subjected to statistical analysis, specifically multiple regression analysis using SPSS. The study’s findings reveal that, contrary to the physical environment, food quality positively and significantly influences consumer satisfaction. This suggests that Robucca Cafe may benefit from placing greater emphasis on maintaining or improving the quality of its food offerings to enhance customer satisfaction. The validity of the study’s indicators has been established through rigorous statistical analysis, further strengthening the credibility of the research findings.